Mechanical Properties of a New Vinyl Polyether Silicone in Comparison to Vinyl Polysiloxane and Polyether Elastomeric Impression Materials - Pandey, Pragya (Contemp Clin Dent, 2019)
BACKGROUND: A new elastomeric impression material which is a combination of vinyl polysiloxane (VPS) and polyether (PE) elastomers called “polyvinyl ether silicone” (PVES) has been introduced with predictable accuracy and high-quality impressions. There is insufficient data on mechanical properties of this material. MATERIALS AND METHODS: A comparative study of mechanical properties of VPS, PE, and PVES was carried out using light- and heavy-body consistencies of the three materials. Three standardized stainless steel molds were made to fabricate study specimens (n = 96). The specimens were tested for elastic recovery, strain under compression, tear energy, and tensile strength (TS) using the universal testing machine. Statistical analysis was done using two-way analysis of variance test. RESULTS: Elastic recovery was higher in VPS as compared to other two materials. Strain under compression was higher for PE followed by PVES. Tensile energy was significantly higher in PVS while TS was higher in VPS, followed by PVES and PE. CONCLUSION: PVES tested was found to be more flexible with high tensile energy. This material can be preferred in cases with undercut areas favoring the removal of impressions without tear and distortion.